Facilitating online learning: students’ online discussion strategies for a project work at a Technical University in Malaysia - Azura Omar,; Zaini Amir,; Maslawati Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The use of online discussion forum is slowly penetrating into classroom teaching and learning as studies have proven that it contributes to a positive learning environment, provided that learners and educators know how to use it effectively. In order to know how to use the online discussion forum effectively, this study was conducted. The research objective was to identify the online discussion strategies employed by the participants. This case study involved fifteen 2nd semester Engineering Technology Malaysian undergraduates enrolled in “Professional English 1” course. Data were gathered from a focus group interview, individual interview and participants’ reflective notes. Five participants volunteered to be interviewed individually and the remainder express their interest to be interviewed in a focus group interview. The participants were interviewed immediately after their online discussion activities. The participants were also asked to reflect to their opinions on their online discussion experience after each online discussion activities. These findings indicate that participants employed three online discussion strategies to facilitate their project work, namely: 1) devising and coordinating ideas before posting 2) interpreting others’ responses before posting their ideas online, and 3) ratifying their own statements before posting. These strategies were employed by the participants to complete a proposal for a Community Service Responsibility (CSR) project. It is hoped that these findings could provide insights and create awareness among the lecturers on the strategies employed by the participants so that more effective and meaningful online discussions could be carried out.